Peddling Protectionism : Smoot-Hawley and the Great Depression - Irwin, Douglas A., 1962- (Book collections on Project MUSE., 2011)
The Smoot-Hawley tariff of 1930, which raised U.S. duties on hundreds of imported goods to record levels, is America's most infamous trade law. It is often associated with--and sometimes blamed for--the onset of the Great Depression, the collapse of world trade, and the global spread of protectionism in the 1930s. Even today, the ghosts of congressmen Reed Smoot and Willis Hawley haunt anyone arguing for higher trade barriers; almost single-handedly, they made protectionism an insult rather than a compliment. In Peddling Protectionism, Douglas Irwin provides the first comprehensive history of.